Improving Teacher Competence in The Implementation of The Merdeka Curriculum: an Intensive Mentoring Approach in Madrasah - Fahrurrozi Fahrurrozi; Nunung Ariandani; Muhammad Marzuki; Nuraini; Laxmi Zahara; Haliliah (TAAWUN, 2025)
The purpose of this community service activity is to provide training to teachers at Madrasah under the auspices of the Yayasan Pendidikan Ridlol Walidain (YPRW) Nahdlatul Wathan Diniah Islamiyah (NWDI) Batu Bangka in implementing the Merdeka Curriculum. The methods of implementing the mentoring that will be carried out are as follows: 1) a Workshop on compiling the madrasah unit curriculum, 2) a Workshop on compiling learning objectives, learning objective flows, and teaching modules, and 3) a Workshop on compiling projects to strengthen the profile of Pancasila students. In addition to the workshop, a mentoring program for the implementation of the three workshops was also carried out. The evaluation results of this community service activity are as follows: 1) 90% of teachers stated that this activity was very satisfied with this community service pattern, 2) the quality of the curriculum products produced was classified as very good, 3) 75% of teachers were able to produce products in the form of TP, ATP, and teaching modules, and 4) the P5 team was able to produce P5 modules with a very good category. From the evaluation results, it can be said that this madrasa could be an example of implementing the Merdeka curriculum.